Influence of Regenerative Tourism Practices on Tourism Performance at Cangkuang Temple: The Role of Cultural Intelligence and Gastronomic Experience - Yusuf Tojiri (Manunggal Halim Jaya, 2026)
Regenerative tourism is increasingly being promoted as a pathway to achieving sustainable and inclusive tourism performance, but its performance outcomes may depend on how visitors interact with local culture and culinary heritage. This study examines whether regenerative tourism practices directly improve tourism performance at Cangkuang Temple and whether this relationship operates through cultural intelligence and culinary experiences as mediating mechanisms and/or is reinforced through their moderating effects. A quantitative design was used with SEM-PLS (SmartPLS) to test the proposed relationships. Data were collected in 2024 from 385 tourists visiting Cangkuang Temple, Garut Regency, Indonesia, using purposive sampling and a 5-point Likert questionnaire. Results indicate that regenerative tourism practices do not significantly affect tourism performance directly, but improve tourism performance indirectly through higher cultural intelligence and enhanced culinary experiences. Furthermore, cultural intelligence strengthens the relationship between regenerative tourism practices and tourism performance, while the moderating effect of gastronomic experiences is not supported. These findings highlight that cultural learning and authentic local culinary encounters are critical levers for transforming regenerative initiatives into better destination performance. Practically, destination managers should integrate cultural interpretation and local gastronomy into regenerative tourism programmes to enhance tourist satisfaction and overall tourism performance.